Body Image and Self-Confidence Correlation Study Between Body Image Perception and Self-Confidence Among Students - Khasali, Dinul Hakkam; Bafadal, Iqbal; Fitriana, Iin Mahlia (Yayasan Alpatih Harapan Semesta, 2024)
Basically, students tend to appear more attractive in order to improve their body image and have good self-confidence. Regarding this, this study aims to determine the relationship between body image and self-confidence in students. This study uses a quantitative correlation approach. The research hypothesis emphasizes the relationship between body image and self-confidence in students. The population criteria were students, with a sample size of 108 people. Data collection tools used body image questionnaires and self-confidence questionnaires with a Likert scale model consisting of 16 items for body image with a coefficient of α = 0.749 and 20 items for self-confidence with a coefficient of α = 0.837. Data analysis emphasized the direction of correlation with a product moment design, with the final result showing a 2-tailed sig value of 0.001 < 0.05 with a Pearson correlation value of 0.322, indicating a low correlation between body image and self-confidence among students.